Political budget cycles and voting within a federal country: the influence of political alignment - Garofalo, Pablo (2020)
We study how distributive politics affects political budget cycles and voting within a federal country. Our model predicts not only that the president favors politically aligned governors with larger transfers, but also that voters favor gubernatorial candidates aligned with the expected presidential incumbent because larger transfers are expected in the future. These predictions are upheld by the data from Argentinean provinces during the 1984–2014 period. Our findings imply that political alignment can trump the selection effect of voting the most competent candidate. This can help explain in particular coattail effects when gubernatorial and presidential elections are concurrent.